Pelaksanaan Program Daring Pendidikan Anak Usia Dini Pada Tk Fast Star Pre-K dan K Kota Ambon ditinjau dari Komponen Contekxt - R. Tutupary (Peneliti.net, 2023)
The purpose of this study is to evaluate the context components in online learning. This type of research is evaluation research using a qualitative descriptive approach, namely research that aims to describe the situation comprehensively in the real context. The results of the study show that in the context component it is known that 1) the vision of the Fast Start Kindergarten Pre-K and K is in accordance with the goals of national education and the institution itself and has involved stakeholders in its preparation. 2) There is a diversity of cultures and educational backgrounds from the teachers giving different thoughts for advancing the PAUD unit. 3) There is leadership support for teachers in implementing online learning